PERILAKU KONSUMSI TREND PAKAIAN DI KALANGAN MAHASISWI (Studi Pada Mahasiswi Sosiologi Fisip UNRI) - Muazzinnur "; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This Study was aimed to investigate the characteristic of female students who prefer toconsume fashion clothing trend that influenced by electronic advertising media and how much itcosts in a year. The population of this study were students of academic year 2012/2013. Whilethe sample of this research is the sociology students. Research sampling is done using simplerandom sampling technique in determining the number of respondents. Data collectiontechniques directly gained through deployment questionnaire as much as 40 questionnaires andnon-participant observation, which is not reach to the level of meanings. Meanings are the valuesbehind the behavior that looks to be spoken and written. The data obtained were then analyzeddescriptively. Then the obtained data were analyzed descriptively.The results of this study indicated that the behavior patterns of fashion clothing trendconsumption are influenced by television ads with the percentage of 32.5%, while the cost ofspending on clothing trend with the percentage of 50.0%, respondents by ages of 20 to 21 with55.0%, residential boarding students with the percentage of 77.5%.Keywords: Consumption Behavior, Trend Clothing, Expenditures, Electronic MediaAdvertising.